Meiosis in allopolyploid Arabidopsis suecica. (22nd July 2022) - Nibau, Candida; Gonzalo, Adrián; Evans, Aled; Sweet‐Jones, William; Phillips, Dylan; Lloyd, Andrew
SUMMARY: Polyploidy is a major force shaping eukaryote evolution but poses challenges for meiotic chromosome segregation. As a result, first‐generation polyploids often suffer from more meiotic errors and lower fertility than established wild polyploid populations. How established polyploids adapt their meiotic behaviour to ensure genome stability and accurate chromosome segregation remains an active research question. We present here a cytological description of meiosis in the model allopolyploid species Arabidopsis suecica (2 n  = 4 x  = 26). In large part meiosis in A . suecica is diploid‐like, with normal synaptic progression and no evidence of synaptic partner exchanges. Some abnormalities were seen at low frequency, including univalents at metaphase I, anaphase bridges and aneuploidy at metaphase II; however, we saw no evidence of crossover formation occurring between non‐homologous chromosomes. The crossover number in A . suecica is similar to the combined number reported from its diploid parents Arabidopsis thaliana (2 n  = 2 x  = 10) and Arabidopsis arenosa (2 n  = 2 x  = 16), with an average of approximately 1.75 crossovers per chromosome pair. This contrasts with naturally evolved autotetraploid A . arenosa, where accurate chromosome segregation is achieved by restricting crossovers to approximately 1 per chromosome pair. Although an autotetraploid donor is hypothesized to have contributed the A . arenosa subgenome to A . suecica, A . suecica harbours diploid A . arenosa variants of key meiotic genes. These multiple lines of evidence suggest that meiosis in the recently evolved allopolyploid A . suecica is essentially diploid like, with meiotic adaptation following a very different trajectory to that described for autotetraploid A . arenosa . Significance Statement: In this manuscript we describe meiosis in the allopolyploid model species Arabidopsis suecica, showing that meiosis, and the genes controlling it, are essentially diploid‐like. Meiotic adaptation in allopolyploid A. suecica therefore follows a very different route to that previously described for autotetraploid A. arenosa.